Comparison and outcomes of dusting versus stone fragmentation and extraction in retrograde intrarenal surgery: results of a systematic review and meta-analysis - TANIDIR, YILÖREN; ŞENER, TARIK EMRE (My University, 2022)
Introduction Lithotripsy during retrograde intrarenal surgery (RIRS) can be achieved either by fragmenta -ti on and extraction or dusting with spontaneous passage. We aimed to perform a systematic review on the safety and stone-free rate after RIRS by comparing the techniques of dusting vs fragmentation/extraction.Material and methods This review was performed according to the Preferred Reporting Items for Systemat-ic Reviews and Meta-analyses statement. The inverse variance of the mean difference and 95% Confidence Interval (CI), Categorical variables were assessed using Cochran-Mantel-Haenszel Method with the random effect model and reported as Odds Ratio (OR) and 95% CI. Statistical significance was set at p <0.05.Results There were 1141 patients included in 10 studies. Stone size was up to 2.5 cm All studies used hol-mium laser for lithotripsy. Meta-analysis showed no significant difference in surgical time (MD-5.39 minutes 95% CI-13.92-2.31, p = 0.16), postoperative length of stay (MD-0.19 days 95% CI-0.60 --0.22, p=0.36), overall complications (OR 0.98 95% CI 0.58-1.66, p = 0.95), hematuria (OR 1.01 95% CI 0.30-3.42, p = 0.99), postoperative fever (OR 0.70 95% CI 0.41-1.19, p = 0.19) and sepsis (OR 1.03 95% CI 0.10-10.35, p = 0.98), immediate (OR 0.40 95% CI 0.13-1.24, p = 0.11) and overall stone-free rate (OR 0.76 95% CI 0.43-1.32, p = 0.33), and retreatment rate (OR 1.35 95% CI 0.57-3.20, p = 0.49) between the groups.Conclusions This systematic review infers that urologists can safely use either option of fragmentation and basket extraction or dusting without extraction to achieve similar outcomes as both techniques are similar for efficacy and safety.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; kidney calculi; lithotripsy; laser; retrograde intrarenal surgery; dusting; fragmentation; LASER LITHOTRIPSY; HOLMIUM LASER; MOSES TECHNOLOGY; RENAL STONES; EFFICIENCY; POWER